Herramientas tecnológicas y su importancia en el desarrollo de las clases virtuales de los estudiantes del 1er curso de bachillerato técnico informática de la Unidad Educativa Prócer José de Antepara periodo 2021- 2022 - Campuzano Romero, Evander Miguel (2022)
The research work deals with the analysis of technological tools and the correct use that should be given to it so that students develop digital skills when obtaining knowledge in online classes. The general objective of this project is to know how digital skills influence the proper development of virtual classes in students of the 1st year of Baccalaureate of the Prócer José de Antepara Educational Unit. For this, it is necessary to know what technological tools are in education and how they influence the cognitive development of each student. This research focuses on the benefits of technological tools in virtual classes and the opportunities that students and teachers can offer if they are administered in the correct way, to achieve this, the first-year students of baccalaureate of the Prócer José de Antepara Educational Unit, resulting in a population of approximately 50 people including students and teachers, the necessary methodological tests were carried out, using as techniques the surveys that consisted of twelve questions carried out by the Google platform in the option of Forms, and interviews were also conducted with the teachers in charge of the students' subjects. All this to verify about themselves both students and teachers knew about the importance of technological tools and the proper use of it, it was also possible to analyze the situation of each student referring to whether they have all the technological devices to be able to develop the skills in technological tools. Finally, the corresponding Tabulation of the surveys carried out was carried out in order to verify the results obtained, taking into account the variety of responses found in the form. As a result of the investigation and analysis of the research consulted by the data collection, we have that the correct use of technological tools is based on the guidance given to the students by the teachers in charge, since of them It depends on the student having a good academic performance and therefore an efficient management of said tools.